Inhibition growth of pomegranate seeds extract against streptococcus sanguis: the cause of recurrent aphthous stomatitis - Riani Setiadhi; Irna Sufiawati; Dewi Zakiawati; Nanan Nur’aeny; Wahyu Hidayat; Dani R. Firman (DiscoverSys Inc., 2017)
Objective : Pomegranate (Punica granatum L.) seeds contain high of phytonutrients and phytochemicals, rich in polyphenol antioxidants namely tannins and flavonoids which also have antibacterial activity. Streptococcus sanguis is a bacterium known as one of the factors causing Recurrent Aphthous Stomatitis (RAS). To examine the potential antibacterial of Pomegranate seeds against Streptococcus sanguis.Material anda Methods : In vitro study of Pomegranate seed were extracted with maceration method using 70% ethanol as the solvent to obtain stable extract, continued with phytochemical screening against phenolic, flavonoids, alkaloids, steroids, triterpenoid, saponins and tannins. Â The extract was evaluated for Minimum Inhibitory Concentration and Minimum Bactericide Concentration against Streptococcus sanguis ATCC 10556, using microdiluted method through 96 wells microplate. Results : Chlorhexidine was used as positive control while 70% ethanol was used as solvent as well as negative control. Phytochemical screening gave positive results for phenolics, flavonoids, steroids, saponins and tannins. Microdilution test showed the concentration of 500 ppm as MIC and MBC value at 2,000 ppm.Conclusion : Pomegranate seeds extract have a growth inhibitory against Streptococcus sanguis with MIC value of 500 ppm and 2,000 ppm as MBC.